Peran Guru Pendidikan Agama Islam dalam Membentuk Kepribadian Siswa di SMP Muhammadiyah 1 Sukoharjo - Miftah Putri Isnan; Suhadi; Yetty Faridatul Ulfah (STIT Sirojul Falah Bogor, 2025)
This study aims to analyze 1) The role of Islamic Education Teachers in shaping Islamic personality, 2) Islamic Education teacher’s efforts in shaping personality, 3) Obstacles and supporting factors in shaping students’ personality at Muhammadiyah 1 Sukoharjo. The type of research was a qualitative approach using descriptive analysis. The research was carried out at Muhammadiyah 1 Sukoharjo with research subjects and informants namely VII grade students, counseling teachers, school principals and Islamic Education teachers. The data collection methods used were interviews, observation and documentation. Data analysis techniques used data collection, data reduction, data presentation and conclusions drawing. The results of research related to the role of Islamic Education Teachers in shaping the personality of students at Muhammadiyah 1 Sukoharjo, include: 1) The role of Islamic Education Teachers, namely teachers as teachers, as good examples, as mentors and as leaders. 2) The efforts made by Islamic Education Teachers in shaping students’ personalities are by giving real examples in daily life, giving good advice, getting students used to saying greetings and shaking hands with teachers, Duha Prayers, Dzuhur Prayers in congregation, Tahfidz, Praying before the lesson starts and before going home. 3) Supporting factors for Islamic Education Teachers in shaping Islamic personality atau Muhammadiyah 1 Sukoharjo Junior High School are teacher support, availability of facilities and infrastructure, student family background and factors from students themselves. Meanwhile the inhibiting factors of Islamic Education Teachers in shaping Islamic personality atau Muhammadiyah 1 Sukoharjo Junior High School are two factors, namely internal factors or from within students themselves and factors from outside students, including lack of parental support, environment and friends hanging out.